2004
DOI: 10.1038/sj.leu.2403376
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of molecular staging by PCR-amplification of immunoglobulin gene rearrangements in diffuse large B-cell lymphoma (DLBCL)

Abstract: The prognostic value of the detection of peripheral blood (PB) and/or bone marrow (BM) involvement by polymerase chain reaction (PCR) amplification of rearranged immunoglobulin heavy chain (IgH) and immunoglobulin kappa light chain (Igj) genes was evaluated in 155 patients with diffuse large B-cell lymphomas (DLBCL). Immunoglobulin gene rearrangements (IgR) were detected in 35/155 (23%) patients. The presence of IgR in PB/BM was related to clinical stage (CS I-III vs CS IV; Po0.001), histopathological detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 37 publications
5
42
1
Order By: Relevance
“…As previously stated, in our study, diagnosis of BM involvement by either m-PTLD or p-PTLD was made based on strict morphologic and phenotypic criteria. While flow cytometry and molecular-based methods are highly sensitive in detecting BM involvement by lymphomas [24,33], these techniques are not well studied in PTLD; and the clinical implications of disease detection only by these more sensitive methods are not known in these patients. Therefore, these techniques were not used for determining BM involvement in our study.…”
Section: Discussionmentioning
confidence: 99%
“…As previously stated, in our study, diagnosis of BM involvement by either m-PTLD or p-PTLD was made based on strict morphologic and phenotypic criteria. While flow cytometry and molecular-based methods are highly sensitive in detecting BM involvement by lymphomas [24,33], these techniques are not well studied in PTLD; and the clinical implications of disease detection only by these more sensitive methods are not known in these patients. Therefore, these techniques were not used for determining BM involvement in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of identical T-or B-cell clones in a tissue sample and in PB is of great importance in staging lymphoid malignancies and is of prognostic relevance. [27][28][29][30] It should, however, be noted that the finding of (oligo)clonality might not always be clinically significant. (Oligo)clonal T-cell populations can be detected in PB of the elderly, 31,32 in patients diagnosed with autoimmune diseases, and in patients with viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…They found a significant difference in overall survival at 5 years in patients with negative histology and negative PCR results (66%), negative histology but positive PCR results (37%), and positive histology as well as positive PCR results (12%). 61 However, they used fresh peripheral blood and BM aspirate samples, and as discussed in previous sections, BM involvement in DLBCL is seen more often on trephine rather than aspirate samples. Previous reports have demonstrated that PCR results correlate better with trephine samples as compared to aspirate samples.…”
Section: Molecular Studies In Dlbclmentioning
confidence: 98%